A versatile electrochemical method to synthesize Co-CoO core-shell nanowires anodes for lithium ion batteries with superior stability and rate capability. (10th November 2018) - Schiavi, Pier Giorgio; Farina, Luca; Altimari, Pietro; Navarra, Maria Assunta; Zanoni, Robertino; Panero, Stefania; Pagnanelli, Francesca
Abstract: A novel electrochemical method is proposed to synthesize nanostructured cobalt electrodes for lithium-ion batteries (LIBs). An array of cobalt nanowires (CoNWs) supported by a nanostructured copper current collector was obtained by the sequential electrodeposition of cobalt and copper into the nanopores of alumina templates and selective etching of alumina. The illustrated method can be implemented with one-side open alumina templates generated by one-step aluminium anodization, thus excluding the application alumina membranes and their coating by sputter metal deposition. The cobalt electrodeposition conditions allow to directly form Co-CoO core-shell nanowires, with metallic cobalt nanowires covered by a thin cobalt oxide film. The direct electrochemical growth of copper nanowires connected to CoNWs ensured high electronic conductivity and specific surface area of the resulting electrode, leading to a low interfacial impedance when used in lithium cell. This nanostructure and the enhanced lithium diffusion enabled by the nanowires morphology contributed to achieve a specific capacity of 1500 mAhg −1 after 200 cycles at 2 Ag -1, and complete restore of the capacity at 2 Ag -1 after cycling at the ultra-high current density of 450 Ag -1 . The faradaic and capacitive contributions to charge storage were estimated by the analysis of cyclic voltammetry experiments carried out at different scan rates. Based on this latter analysis, pseudo-capacitive effects appear to play a pivotal role in determining the total recorded capacity. The advantages of the proposed method to sustain the large scale application of nanowires electrodes in lithium batteries are thoroughly discussed.